Ocular Morbidity among Street Children in Kathmandu Valley. (December 2014) - Pant, Mukund; Shrestha, Gauri Shankar; Joshi, Niraj Dev
Abstract Purpose: Prevalence of ocular morbidity among street children is largely unknown. The present study was carried out to determine the prevalence of ocular morbidity among street children in the Kathmandu Valley. Methods: A cross-sectional study consisting of an eye examination program among 569 street children aged younger than 18 years was conducted from March 2013 to February 2014. Children were included from 11 safe houses of 6 non-governmental organizations and an independent eye camp. Eye examination included visual acuity testing, anterior segment and posterior segment examination, retinoscopy and refraction, cover test, convergence, accommodation and color vision tests. Chi-square test was used to analyze the association of ocular morbidity with age, sex and living conditions. Results: The majority of children (43.8%) were in the age group of 12–15 years, and the male to female ratio was 3.9:1. Uncorrected and best-corrected visual acuity ≥6/9 in at least one eye was found in 89.8% and 98.4% of children, respectively. Total ocular morbidity was observed at 31.6%. The most common types of ocular morbidity were conjunctivitis (11.0%) and refractive error (11.6%). Ocular morbidity was more common in children over 15 years of age (40.9%; p < 0.01; odds ratio 1.8). Conclusions: Ocular infection and refractive error represent the most common ocular morbidities in street children in the Kathmandu Valley.